Implementasi Konsep Good Samaritan Law Sebagai Alternatif Perlindungan Tenaga Medis dan Tenaga Kesehatan dalam Pelayanan Kegawatdaruratan - Inna Noor Inayati (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Medical emergency services demand swift and precise action; however, medical personnel are often hindered by the risk of criminalization resulting from unintended outcomes. Although Law Number 17 of 2023 concerning Health mandates the provision of assistance, the regulation has not yet provided explicit criminal protection for good-faith rescuers, thereby triggering the practice of defensive medicine. This study aims to examine the implementation of the Good Samaritan Law (GSL) concept as an alternative legal protection for health workers. The research methods employed are juridical-normative and juridical-empirical, utilizing statutory, comparative, and case approaches. The findings indicate that current regulations, including Article 531 of the Criminal Code (KUHP) and Law No. 17/2023, have limitations as they emphasize the obligation to assist rather than the protection of the rescuer. In comparison, the international GSL concept offers a standard of "limited immunity," which explicitly protects rescuers from civil and criminal liability, provided the actions are performed without gross negligence. The impact of implementing GSL in Indonesia is projected to provide stronger legal certainty than existing regulations, reduce the psychological burden on medical personnel in emergency situations, and encourage social solidarity without the fear of unnecessary lawsuits. The study concludes that the adoption of GSL is an urgent legal reconstruction to ensure the professional protection of health workers in Indonesia.